2020
DOI: 10.1108/ijebr-08-2019-0505
|View full text |Cite
|
Sign up to set email alerts
|

Testing mediating effects of individual entrepreneurial orientation on the relation between close environmental factors and entrepreneurial intention

Abstract: PurposeDrawing on the literature on entrepreneurial intention (EI), this paper develops and tests a model that aims to explain student EI by considering the valuation of entrepreneurship and the venture failure stigmatization in the closer environment of the respondent and the role of individual entrepreneurial orientation (IEO) through direct and indirect effects.Design/methodology/approachThe paper uses a survey method for data collection. As such, this study was conducted by considering a sample of 1,155 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
2
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 106 publications
4
78
2
7
Order By: Relevance
“…IEO is considered an entrepreneurial competency that can be developed through experiential learning (Sahoo and Panda, 2019). Recent studies show a positive relationship between IEO and EI (Ekpe and Mat, 2012; Martins and Perez, 2020; Robinson and Stubberud, 2014; Zhang and Bruning, 2011). Ibrahim and Lucky (2014), for example, studying Nigerian students at the University of Malaysia, found a positive and significant relationship between IEO and EI.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…IEO is considered an entrepreneurial competency that can be developed through experiential learning (Sahoo and Panda, 2019). Recent studies show a positive relationship between IEO and EI (Ekpe and Mat, 2012; Martins and Perez, 2020; Robinson and Stubberud, 2014; Zhang and Bruning, 2011). Ibrahim and Lucky (2014), for example, studying Nigerian students at the University of Malaysia, found a positive and significant relationship between IEO and EI.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 98%
“…Ibrahim and Lucky (2014), for example, studying Nigerian students at the University of Malaysia, found a positive and significant relationship between IEO and EI. Literature is available on EO as a firm-level construct, with many studies having been conducted on its relationship to business performance, but because IEO is a more recent conceptualization, there is comparatively little literature on the construct (Martins and Perez, 2020). This study therefore adds to the existing limited literature on the relationship between IEO and EI by examining the following hypothesis: H1: Individual entrepreneurial orientation positively influences entrepreneurial intention. …”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Entrepreneurial intention is defined as the self-belief of individual to provide new venture creation or enhances the value-added of the current business (Vuorio et al, 2018). Therefore, the questions on what or how to enhance entrepreneurial intention as well as preparing for business have raised attention among scholar and policymakers in various countries (Jena, 2020;Kusumojanto et al, 2021;Martins & Perez, 2020). Based on the viewpoints of social cognitive theory, individuals tend to pursue their own targets only when they believe their abilities and actions can achieve the expected results (Bandura, 2018).…”
Section: Entrepreneurial Intention and Prepare For Entrepreneurshipmentioning
confidence: 99%
“…Research has found that entrepreneurial training, which provides specific skills and abilities, as such, innovative, proactiveness, and risk-taking behaviour to students has proven to promote student's entrepreneurial intention (Martins & Perez, 2020). However, it is still a lack of studies concentrated on computers and internet capabilities and entrepreneurial behaviour (Arshad, Rasli, Arshad, & Zain, 2014;Ratten, 2013).…”
Section: Literature Review Individual Entrepreneurial Orientation (Ieo)mentioning
confidence: 99%
“…Thus, forming an individual's entrepreneurial behaviours not only being innovative thinking but also have the ability to analyzed internally and externally and generate opportunities continuously. Therefore, various skills needed forIEO can be developed (Martins, Monsalve, & Martinez, 2018;Martins & Perez, 2020).…”
Section: Literature Review Individual Entrepreneurial Orientation (Ieo)mentioning
confidence: 99%